High-resolution marine data and transient simulations support orbital forcing of ENSO amplitude since the mid-Holocene - Carré M. (2021)
This research has been supported by the JPI-Belmont project PACMEDY (via grant ANR-15-JCLI-0003-01 for MC, PB, ME, OM, TC, and BT). MC, JC, DO, RSG, AP, and PR acknowledge funding from Concejo Nacional de Ciencia y Tecnologia de Peru (grant n° 007-2017-FONDECYT , grant n° 034-2019-FONDECYT-BM ). SPH acknowledges funding from the ERC-funded project GC2.0 Global Change 2.0: Unlocking the past for a clearer future, grant number 694481 and from the JPI-Belmont project PACMEDY (via NERC ). The distribution and analyses of the transient Holocene simulations with the IPSL model benefit from the Institut Pierre Simon Laplace Climate Modeling Centre Infrastructure supported by ANR “Investissements d'avenir” program ANR-11-IDEX-0004-17-EURE-0006 .